2005
DOI: 10.1111/j.1365-3156.2005.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide poisoning in south India: opportunities for prevention and improved medical management

Abstract: Summary Objective  Warangal district in Andhra Pradesh, southern India, records >1000 pesticide poisoning cases each year and hundreds of deaths. We aimed to describe their frequency and distribution, and to assess quality of management and subsequent outcomes from pesticide poisoning in one large hospital in the district. Methods  We reviewed data on all patients admitted with pesticide poisoning to a district government hospital for the years 1997 to 2002. For 2002, details of the particular pesticide ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(81 citation statements)
references
References 21 publications
11
64
1
Order By: Relevance
“…18 In this study, we observed that out of 111 patients, 60% were males, and 85.6% were within the age limit of 12-30 years. These observations are consistent with the results of Srinivas, et al 19 In his study, males outnumbered females (57% vs. 43%) with all types of pesticides including organophosphorus compounds and two-thirds of them were less than 30 years of age. Similarly in the studies by Safdar 20 , Fahmi and Aziza 21 , number of male victims was higher than females.…”
Section: Discussionsupporting
confidence: 82%
“…18 In this study, we observed that out of 111 patients, 60% were males, and 85.6% were within the age limit of 12-30 years. These observations are consistent with the results of Srinivas, et al 19 In his study, males outnumbered females (57% vs. 43%) with all types of pesticides including organophosphorus compounds and two-thirds of them were less than 30 years of age. Similarly in the studies by Safdar 20 , Fahmi and Aziza 21 , number of male victims was higher than females.…”
Section: Discussionsupporting
confidence: 82%
“…In parts of northern India, aluminum phosphide causes most deaths in epidemic that started two decades ago. 2 Cases of acute pesticide poisoning (APP) cause significant morbidity and mortality worldwide especially in developing countries. There is no reliable estimate as how many persons per year suffer from pesticide related health effects this is due to several reasons including lack of standardized case definition.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, variety of complication were observed (Table 12). [12][13][14][15][16] Individuals in this age group are active physically, mentally and socially and thus more prone to various stresses. The present study had more number of illiterate and those studied below intermediate level with majority of cases being related directly or indirectly to farming.…”
Section: Variablementioning
confidence: 99%